The Dose-Related Efficacy of Acupuncture on Endometrial Receptivity in Infertile Women: A Systematic Review and Meta-Analysis - Zheng, Xiaoyan; Yu, Siyi; Liu, Liying; Yang, Han; Wang, Fangge; Yang, Hongmei; Lv, Xingyu; Yang, Jie (Frontiers in Public Health, 2022)
Background: Progress has been achieved by using acupuncture widely for poor endometrial receptivity (PER). However, different acupuncture dosages may lead to controversy over efficacy. Objective: To evaluate the evidence-based conclusions of dose-related acupuncture on infertile women with PER. Method: References were retrieved in nine databases from inception to Feb 26, 2022. This meta-analysis included randomized controlled trials (RCTs) which investigated the dose-related efficacy of acupuncture for PER with outcomes of endometrium receptivity (ER) parameters by transvaginal sonography (TVS) and the subsequent pregnancy outcomes in three acupuncture-dose groups: the high dosage group (three menstrual cycles), the moderate dosage group (one menstrual cycle), and the low dosage group (2 or 4 days). Since there remained sufficient heterogeneity among the three subsets, we prespecified 7 subgroup variables (4 clinical and 3 methodological) to investigate the heterogeneities. Results: 14 RCTs (1 564 women) of moderate or low overall quality were included. The results were different when the dosage of acupuncture was restricted. For the moderate or high dosage group, CPR and part of ER parameters were improved in the acupuncture group (i.e., CPR: OR=2.00, 95% CI [1.24,3.22], P=0.004, I2=0% in one menstrual cycle; OR=2.49, 95%CI [1.67,3.72], P<0.05, I2=0% in three menstrual cycles). However, for the low dosage group, no statistical difference was observed in CPR (OR=0.07, 95% CI [-0.10,0.23], P=0.44, I2=82%), and part of ER parameters. In subgroup analysis, 4 subgroup variables (the routine treatment, risk of performance bias, duration of acupuncture treatment, and the age of participants) could explain some of the heterogeneities across all trials. Conclusion: The finding indicated that the trend of relatively more acupuncture dosage showed better effects for poor endometrial receptivity among PER women. It remains potential heterogeneities in our studies. Further high-quality trials with a homogeneity trial design need to be conducted.